2013
DOI: 10.4081/mrm.2013.539
|View full text |Cite
|
Sign up to set email alerts
|

A pulmonary rehabilitation program reduces levels of anxiety and depression in COPD patients

Abstract: Background: The presence of anxiety and depressive symptoms in COPD patients has been acknowledged for many years. The preponderance of recent studies supports the utility of pulmonary rehabilitation programs to reduce the levels of depression and anxiety in these patients. The aim of this study is to investigate possible changes in levels of anxiety and depression among patients enrolled in a pulmonary rehabilitation program, along with the role of disease severity in these changes. Methods: In 101 COPD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
2
19
0
5
Order By: Relevance
“…In addition, PR has been shown to have a beneficial effect in reducing anxiety and dyspnea, also reported to be common in mild-to-moderate patients. [14,38] We observed similar improvements in anxiety and depression scores in both groups after intervention.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, PR has been shown to have a beneficial effect in reducing anxiety and dyspnea, also reported to be common in mild-to-moderate patients. [14,38] We observed similar improvements in anxiety and depression scores in both groups after intervention.…”
Section: Discussionsupporting
confidence: 61%
“…The published prevalence rates for depression in COPD patients vary widely [38] but some estimates of depression in COPD patients are around 50% for severe COPD, approximately 2.5 times greater than age-matched control population [39]. It has been shown that state anxiety is associated with worse functioning on measures of exercise performance, HRQL and shortness of breath in patients with moderate to severe emphysema [40].…”
Section: Psychological Statusmentioning
confidence: 99%
“…37,38,53 Alarmingly, one study found in a population of VA patients with a high prevalence of COPD and depression that only 50.6% of these individuals were adequately treated for their depressive symptoms, 60 while another group provided lower estimates of 27 to 33% of COPD patients receiving treatment of any form for their depression. 61 Though there are few studies that have looked at the impact of pharmacotherapy for depression on outcomes in COPD, 48,62 there have been a few more which have shown that pulmonary rehabilitation programs show some promise in improving depressive symptoms, 51,[63][64][65] dyspnea, 64 quality of life, 66 and exercise capacity 51 in patients with depression and COPD. Regardless, it has been shown that depressive symptoms are a risk factor for nonadherence to maintenance exercise programs in COPD patients, 67 further demonstrating the challenge of treating this population of patients.…”
Section: Chronic Obstructive Pulmonary Disease and Depressionmentioning
confidence: 99%